ANALISIS LOGAM ESENSIAL DAN SENYAWANYA DALAM SEDIAAN MENGGUNAKAN METODE DIFRAKSI DAN FLUORESENSI SINAR - X. - Mursito, Bambang
The analysis of a mixture of metallic compounds in a dosage form has been carried out by X-ray diffraction and fluorescence methods. Single crystalline metallic compound could be analyzed by X-ray diffraction method, while in a mixture, identification could be done as long as each component showed high intensity diffraction lines of different d values. A mixture of zinck, copper, cobalt, manganese, iron, calsium, potassium and magnesium in tablet dosage form could be identified simultaneusly by X-ray fluorescence method. The recovery of 0. 050%, 0.125%, 0.250%, 0.50% and 1.0% of copper was 114±50.4%, 109.3±4.8%, 107.5±3.6%, 111.3±3.7% and 105.5±1.1%, respectively and that of 0.4%, 1.0%, 2. 0%, 4.0%, and 8.0% of calcium was 102.5±2.5%, 100.5±1%, 101.6±2,9%, 98.6 ±0. 4% and 98.3±0.6%, respectively. This method couldn\'t differ the oxydation state of metal.